Principal Component Analysis Applied To The Heuristic Evaluation Of The Quality Of Websites Of Universities - Palacios-Zamora, Kerly; Córdova-Morán, Jorge; Pacheco-Mendoza, Silvia; Guerra-Gaibor, Jessica (Migration Letters, 2024)
In the present research endeavor, the assessment of the quality of websites belonging to Ecuadorian universities is posited. To facilitate this assessment, a heuristic tool has been formulated, drawing upon contributions from various authors, Given the absence of a singular methodology within this research domain for appraising the quality of these digital platforms. This involves the analysis of content derived from official websites, applying an evaluation form composed of 55 indicators that verify the existence and functionality of digital resources. As an additional contribution, the information has been processed using Principal Component Analysis to identify components capable of explaining the variability in the data, Furthermore, HJ-Biplot graphs have been utilized to pinpoint multivariate covariation structures among the quality indicators employed. The scrutiny extended to the official websites of all 62 accredited universities in Ecuador. Notably, the analysis revealed that 6 components contribute to over 53% of the variability in the data. This outcome has facilitated the identification of the most pertinent indicators crucial for evaluating the quality of the examined websites. Similarly, the results of this study highlight that well-conceived web design is characterized by being intuitive, accessible, and functional, with special attention to communication and interaction with the university community